Fatores de risco para recidiva de lesões intraepiteliais cervicais em pacientes infectadas e não-infectadas pelo HIV, submetidas a conização por cirurgia de alta freqüência - Claudia Teixeira da Costa Lodi (2009)
Objective: To evaluate the risk factors for cervical intraepithelial neoplasia recurrence, in human immunodeficience virus (HIV)-infected and noninfected women who underwent the loop electrosurgical excision procedure (LEEP). Methods: Case-control of 33 patients with cervical intraepithelial neoplasia (CIN) recurrence (cases) and 105 without recurrence (controls), HIV infected and noninfected, treated with LEEP, between january 1999 and may 2004. The diagnosis of recurrence was established after biopsy. Polymerase chain reaction (PCR) was used to detect human papillomavirus genome (HPV DNA), with consensus primers for low-risk types 6,11, and high-risk types 16,18,31,33,35, informalin-fixed, paraffin-embedded cone specimens. Statistical analysis were performed using X2 test with Yates correction and Fisher's exact test for comparison of categorical variables. Multivariate analysis was carried out using a logistic regression, keeping only significant variables (p< 0,05) , in the final model. Results: Recurrence was more frequent in women HIV-infected (p=0,001) with glandular involvement (p=0,000) and compromised margins (p=0,02). HPV DNA was positive in 57,6% patients with CIN recurrence and 36,4% remained HPV DNA negative. High-risk HPVs were detected in most cases. HPVs 6,11,16,18,31,33,35 weren't associated with recurrence (p=0,27). A multivariate analysis showed that HIV-infection and glandular involvement were independentlyassociated with recurrence of lesions. Compromised margins were interrelated with glandular involvement. Conclusions: Recurrence rate of CIN in HIV-infected women was higher than in HIV-negative women. The factors associated with recurrence were HIV infection and glandular involvement in cone biopsy.